Psychological and Emotional Challenges Faced by Female HIV Counselors in Kashmir—A Phenomenological Study - Khalid Bashir MBBS, MD; Inaamul Haq MBBS, MD; Mariya Amin Qurieshi MBBS, MD; S. Muhammad Salim Khan MBBS, MD (Journal of the International Association of Providers of AIDS Care)
Background Human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) counselors play a crucial, albeit challenging, role in preventing and controlling HIV. People living with HIV (PLHIV) need emotional support in addition to clinical treatment. Counseling is more difficult for female counselors, considering the psychological and emotional aspects of HIV counseling. Methodology A qualitative study design was used to understand the complexity of the challenges faced by female HIV counselors. Interpretative phenomenological analysis (IPA) was employed as the research design. A small, homogeneous sample was purposively selected, comprising all 11 female HIV counselors in the Kashmir province and one female counselor in Leh (Ladakh). The IPA methodology was utilized, which emphasizes meaning-making and understanding the counselor's perspectives. The study was conducted from December 2022 to January 2023, with data collected through in-depth interviews at the counselors’ workplaces and via Zoom for the Leh participant. Data were analyzed thematically using the IPA approach, revealing the counselors’ real-life experiences, perceptions, and challenges. Results The analysis generated two superordinate themes with multiple overarching themes and sub-themes: Intrusive emotional and psychological experiences: Counselors experienced significant emotional strain, including emotional exhaustion, burnout, and stigma. Inadequate skills for effective counseling of people who inject drugs (PWID): Limited training hindered effective counseling for substance users and PWID, highlighting the need for specialized training. Conclusion Female HIV counselors in Kashmir face numerous psychological and emotional challenges, including emotional exhaustion, burnout, and stigma. Additionally, there is a lack of adequate training for counseling substance users. Addressing these issues through specialized training, stigma reduction initiatives, and mental health support is crucial for improving HIV counseling services and the overall HIV/AIDS response in the region.